1990
DOI: 10.1002/pssb.2221570225
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties and Nature of Coordination of Cu+ Ions in Calcium Metaphosphate Glass

Abstract: Absorption, emission, and excitation spectra of copper(1) ions in calcium metaphosphate glass are investigated. Analysis of the absorption spectrum in the light of ligand field theory reveals that the oxygen coordination surrounding the ion in glass is grossly a trigonally distorted octahedron. A chemical model for the copper(1) ion site in glass is proposed and the mode of distortions that brings about strong tfigonal fields a t the central ion is discussed. The lowest triplet (sEg) in the system is identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…Because the quantum yield was measured to be 2 to 3% in this study, the radiative component was calculated to be 25 ± 5 μs, which is in agreement with the low-temperature studies. The long-lived radiative component is very similar to that of the triplet state emission observed in Cu + -doped glasses at room temperature, which was measured to be 41 μs . It is, therefore, likely that the dopant emission in these systems involves a triplet as well; however, direct evidence of this has not been reported.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Because the quantum yield was measured to be 2 to 3% in this study, the radiative component was calculated to be 25 ± 5 μs, which is in agreement with the low-temperature studies. The long-lived radiative component is very similar to that of the triplet state emission observed in Cu + -doped glasses at room temperature, which was measured to be 41 μs . It is, therefore, likely that the dopant emission in these systems involves a triplet as well; however, direct evidence of this has not been reported.…”
Section: Resultssupporting
confidence: 56%
“…The long-lived radiative component is very similar to that of the triplet state emission observed in Cu + -doped glasses at room temperature, which was measured to be 41 μs. 90 It is, therefore, likely that the dopant emission in these systems involves a triplet as well; however, direct evidence of this has not been reported.…”
Section: Structure and Composition: Xrd Tem And Icpmentioning
confidence: 99%
“…Optical absorption studies of copper ions in phosphate glasses [29,30] indicate that Cu 2+ ions occupy octahedral sites. Also, UV absorption and emission studies [31] indicate that Cu + ions in calcium phosphate glasses exist in trigonally distorted octahedra. Octahedral coordination environments of both Cu + and Cu 2+ will be assumed to be the preferred co-ordination of copper ions in the binary copper ultraphosphate glasses in this study.…”
Section: Discussionmentioning
confidence: 98%
“…This absorption experimentally indicates that copper ions seem to be present in the studied host lead phosphate glass mostly as Cu + ions revealing no broad visible band in the range 750-1000 nm which is characteristic for Cu 2+ ions. Some authors [43,44] have suggested and identified the presence of Cu + ions in some phosphate glasses and assumed their existence in trigonally distorted octahedral coordination and exhibiting ultraviolet bands. Denath et al [43] have suggested that the position of Cu + ion absorption is at 215 and 243 nm while Ehrt and Brettschneider [44] have proposed them at 175 and 230 nm.…”
Section: Interpretation Of the Absorption Spectra Due To Tms Ions Andmentioning
confidence: 99%
“…Some authors [43,44] have suggested and identified the presence of Cu + ions in some phosphate glasses and assumed their existence in trigonally distorted octahedral coordination and exhibiting ultraviolet bands. Denath et al [43] have suggested that the position of Cu + ion absorption is at 215 and 243 nm while Ehrt and Brettschneider [44] have proposed them at 175 and 230 nm. On the basis of such postulations, it can be assumed that the experimentally observed very broad UV bands are due to the possible sharing of absorption due to the presence of collective sharing of Pb 2+ ions, trace iron impurities and Cu + ions inspite of the appearance as weak peaks.…”
Section: Interpretation Of the Absorption Spectra Due To Tms Ions Andmentioning
confidence: 99%